O estágio supervisionado em coordenação e gestão escolar na Escola Municipal de Ensino Fundamental José Pereira Gomes em Primavera-PA: o planejamento como suporte pedagógico - FERREIRA, Lorena Nascimento (2023)
This Course Completion Work is the result of the experiences lived in the performance and direct dialogue with the coordination and management at the Municipal Elementary School José Pereira Gomes, located at Travessa Sete de Setembro, Centro neighborhood, in the city of Primavera, in the Supervised Internship in Management and Pedagogical Coordination of the Pedagogy Course at the Faculty of Education, Campus Universitário de Bragança, Universidade Federal do Pará. to reflect on how the pedagogue will act in these workspaces, making a dialogue with academic works, by theorists, such as Menegolla & Sant'Anna (2014), Dalmás (1994), Lopes (et al. 2019) among others, who build research in the theoretical field in which this study is inserted. For this, a qualitative research methodology Minayo (2007) (1994) was used, with the intention of combining opinions and experiences of the internship supervisors, the appropriate bibliographic material for the construction of an information network about how the internship occurs. performance of pedagogues in this school. In addition, the Marietto (2018), Queiroz (2007) method and participant observation was used to develop a more harmonious dialogue with members of different instances of the school. It is concluded that there are many challenges and difficulties encountered by the pedagogy professional in these spaces, being necessary for him to constantly re-signify his practice and his pedagogical know-how to meet the educational needs of the school and the community that guides it.